Referat Jumlah Leukosit sebagai Prediktor Perburukan Trombositopenia pada Pasien Demam Dengue Anak - Retno Wisanti; Vica Natalia Gonga; Wijaya Hartanto; Wijayanti Diyah Ayuningsih (Jurnal Health Sains, 2022)
Dengue fever (DF) and its severe form, dengue hemorrhagic fever (DBD) and dengue shock syndrome (DSS) have become major international public health problems. Over the past three decades, there has been a dramatic global increase in the frequency of dengue fever (DF), DENGUE and DSS and their epidemics, with concurrent increases in the incidence of the disease. This study is an observational analytical study, intending to analyze the relationships between variables. The research design used is cross sectional. The study used semi-quantitative methods with medical record data. Statistical tests (Fisher's test) are conducted to analyze the number of leukocytes as a predictor of thrombocytopenia worsening. From the results of the test obtained p = 0.009 (p<0.05) which means the number of leukocytes can be used as a predictor of worsening thrombocytopenia in pediatric dengue fever patients.  Conclusions that can be drawn from this study there is an influence between the number of leukocytes and predictors of thrombocytopenia worsening with a significance value (p) of 0.009 < (α) 0.05 which means there is significance between the number of leukocytes and the worsening of thrombocytopenia, so that the number of leukocytes can be used as a predictor of worsening of thrombocytopenia in pediatric dengue fever patients